2020
DOI: 10.3389/fphar.2020.577124
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Applications, Phytochemistry, and Pharmacological Activities of Eupatorium lindleyanum DC.: A Comprehensive Review

Abstract: Eupatorium lindleyanum DC. (EL) has a long history of traditional use in China to cure coughs, chronic bronchitis, lobar pneumonia, and hypertension. Because of this extensive use of EL in traditional medicine, this present review gives a systematic overview of the conventional applications, phytochemistry, and pharmacological effects of the herb. Literature was systematically searched using the scientific databases ScienceDirect, SciFinder, CNKI, Wiley, Baidu Scholar, SpringerLink, PubMed, Web of Science, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Eupalinolide A (EA) and eupalinolide B (EB), a pair of cis-trans isomers ( Figure 1 ), are bioactive sesquiterpenoids found in Eupatorii Lindleyani Herba ( Wang X. et al, 2020 ). As potential drug candidates, these isomers have been reported to exert anti-inflammatory and antitumor effects ( Zhang et al, 2022a ; Zhang et al, 2022b ; Yang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eupalinolide A (EA) and eupalinolide B (EB), a pair of cis-trans isomers ( Figure 1 ), are bioactive sesquiterpenoids found in Eupatorii Lindleyani Herba ( Wang X. et al, 2020 ). As potential drug candidates, these isomers have been reported to exert anti-inflammatory and antitumor effects ( Zhang et al, 2022a ; Zhang et al, 2022b ; Yang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eupatorium lindleyanum DC. (EL), also called 'Yemazhui', is a traditional Chinese medicine that has been used to treat cough and chronic bronchitis in China for several thousands of years ( 8 ). Scientists have isolated >100 compounds from EL, including sesquiterpenes, diterpenoids, triterpenoids and volatile oils, and sesquiterpenes are one of the most abundant ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…11 Importantly, EL preparations, such as Eupatorium Kechuan powder and Yemazhui capsule, are clinically applied to treat respiratory diseases. 7 F1012-2 is a novel, active, sesquiterpene lactone fraction isolated from EL. In our previous study, we reported that F1012-2 had significant anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…(EL), also called "Yemazhui," has the effects of "clearing heat to remove toxicity," and is widely used to treat cough and chronic bronchitis for various ages in China. 7 A great number of studies have proved that EL has many pharmacological activities, including anticancer, 8,9 antiviral, 10 and anti-inflammatory. 11 Importantly, EL preparations, such as Eupatorium Kechuan powder and Yemazhui capsule, are clinically applied to treat respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%